Crime lab chemistry : teacher's guide - Barber, Jacqueline (Berkeley, CA : University of California at Berkeley, 1985)
Presents a chemistry unit for grades four through eight in which students are charged with using scientific concepts, methods, and techniques in an effort to determine which black pen was used to write a ransom note.
Grades 4-8.
Professional
Keywords: Chemistry, Forensic -- Study and teaching (Elementary); Chemistry -- Experiments; Paper chromatography; Chemistry -- Experiments; Chemistry -- Study and teaching